Training process design in weightlifting sports customized to genetic predispositions - Aksenov, M. O.; Ilyn, A. B. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to provide theoretical grounds for the training and competitive loads to be optimized within the frame of the long-term training process design in weightlifting sports in view of the athletes' individual genetic predispositions. We explored associations of the ACE, ACTN3 and PPARGC1A gene polymorphisms with the quantitative and qualitative parameters of the training process in weightlifting sports. Our analysis of the allele frequency for ACE, ACTN3 and PPARGC1A genes made it possible to expand our knowledge of the types of bodily adaptation to training loads. We found the genetic effects being significant for the sport mastery progress rates. We assumed the genetic factors being of effect on the individual competitive success forecasts within the frame of the long-term training process in weightlifting sports. We developed and implemented new methods designed to analyze and plan training loads versus relevant qualitative and quantitative progress parameters. New training and competitive load rating algorithms were offered for the weightlifting sports. We offered theoretical grounds for the training process design to facilitate the efforts to develop and implement new training methods to attain goals of the training and competitive process as required by the physical fitness and sport mastery improvement mission. We used the experimental data to develop the training and competitive load integrated rating method. The proposed training and competitive load rating algorithm makes it possible to clearly and simply rate the training process efficiency with the training loads being harmonized with the actual athletes` training capacity levels in every physical training domain. The study found the ACE, ACTN3 and PPARGC1A genotypes in Masters of Sport and World Class Athletes in weightlifting, and the finding makes it possible to customize athletes' training loads by variations of the qualitative and quantitative parameters of the training loads. The study findings were proved beneficial for the training process design in the weightlifting sports.